1984
DOI: 10.2337/diab.33.3.271
|View full text |Cite
|
Sign up to set email alerts
|

The Pittsburgh Insulin-dependent Diabetes Mellitus (IDDM) Morbidity and Mortality Study: Mortality Results

Abstract: A follow-up study of 1966 patients with insulin-dependent diabetes mellitus (IDDM) who were diagnosed at Children's Hospital of Pittsburgh (CHP) between 1950 and 1981 has been completed. The mean age of the population at follow-up was 21.2 yr with a mean duration of IDDM of 12.9 yr. Nine percent of the patients were deceased, a sevenfold excess in mortality compared with the U.S. population. The relative increase in mortality was greater for females than males and greater for blacks than whites. Before age 20,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
156
3
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(174 citation statements)
references
References 0 publications
13
156
3
2
Order By: Relevance
“…Although an increased risk of heart disease is well recognised as a chronic complication of diabetes, agespecific mortality statistics for death from IHD have not been previously reported in patients with Type 1 diabetes, perhaps because published cohorts have been too small [9,10,16]. We have shown that in patients with Type 1 diabetes IHD mortality rates are raised in comparison with the general population at all adult ages, and in both sexes.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Although an increased risk of heart disease is well recognised as a chronic complication of diabetes, agespecific mortality statistics for death from IHD have not been previously reported in patients with Type 1 diabetes, perhaps because published cohorts have been too small [9,10,16]. We have shown that in patients with Type 1 diabetes IHD mortality rates are raised in comparison with the general population at all adult ages, and in both sexes.…”
Section: Discussionmentioning
confidence: 57%
“…Within the past 30 years there have been a number of studies quantifying the risk of IHD mortality but these have been mainly restricted to patients with Type 2 diabetes [3,4,5,6] or have included patients with Type 1 and Type 2 diabetes together [7,8]. Although CVD is also recognised as a complication in patients with Type 1 diabetes [9,10], mortality from IHD has been less frequently studied and IHD mortality risks by age and sex have not been reported for these patients.…”
mentioning
confidence: 99%
“…Since there were some differences in demographic characteristics between the two cohorts as presented in Table 1 and these characteristics have been previously found to be associated with overall mortality [13,14], they were included in multivariate models to adjust for their independent effect. The Cox proportional hazard model was employed to adjust for sex, age at onset, calendar year of onset, and duration of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Type 1 diabetes confers a twoto tenfold increased risk of death and cardiovascular disease compared with the background population [1,2]. Diabetes is associated with endothelial dysfunction and reduced neovascularisation in response to tissue ischaemia [3,4].…”
Section: Introductionmentioning
confidence: 99%